Side effects of drugs annual. a worldwide yearly survey of new data in adverse drug reactions - Ray, Sidhartha D. (Side Effects of Drugs Annual ;, 2018)
Side Effects of Drugs Annual: A Worldwide Yearly Survey of New Data in Adverse Drug Reactions, Volume 40, first published in 1977, and continually published as a yearly update to the voluminous encyclopedia Meyler's Side Effects of Drugs, presents clinicians and medical investigators with a reliable and critical survey of new data and trends in the area of adverse drug reactions and interactions, with an international team of specialists contributing each year. Topics covered in this release include Central Nervous System Stimulants and Drugs that Suppress Appetite, Antidepressant drugs, Lithium, Drugs of abuse, Hypnotics and sedatives, Antipsychotic Drugs, and much more.